Italian Literature, Volume 3, Il Tristano Corsiniano - Allaire, Gloria 1954-; Allaire, Gloria 1954- (Boydell & Brewer, 2015)
This is the first English translation of the earliest Italian Tristan romance, the Tristano Riccardiano, preserved in MS. 2543 of the Biblioteca Riccardiana in Florence. In Italy, Tristan was more popular than any other Arthurian hero; the French prose Tristan gained great currency, soon yielding Italian prose translations / adaptations. The Riccardiano, dating from the late thirteenth century, is notable for representing an early branch of the French prose Tristan, now lost. The translation offers new evidence for the development of the Tristan story in Europe, particularly in the changes it rings on the themes of love, chivalry, honour, betrayal, and adultery. In theme and narrative style the Riccardiano reflects a new audience and a new social context, that of an urban Tuscan middle class, and an important stage in the emergence of Italian prose narrative. Apparatus includes an introduction, a select bibliography, a synopsis of the romance, an index of proper names